ARM Instructions Part I - Elahi, Ata; Arjeski, Trevor (ARM Assembly Language with Hardware Experiments, 2015)
Advanced RISC Machine (ARM) was developed by the Acorn Company. ARM is a leader supplier of microprocessors in the world, ARM develop the core CPU and thousand of suppliers add more functional units to the core. ARM uses two types instruction called Thumb and Thumb-2. Thumb instructions are 16 bits and thumb-2 instructions are 32 bits, currently most ARM processors uses 32 bit instructions.
Citation Key Alias: lens.org/004-692-447-907-924
Keywords: dept.csc